Estimating mobility and lifetime of charge carriers in semiconductor detectors using Genetic Algorithms. (30th June 2010) - Shaaban, Noha
A Genetic Algorithm (GA) was adopted to extract realistic values of the transport properties of both electrons and holes in semiconductor materials. A theoretical waveform model was fitted to the real digitised signal waveform taking into account the realistic transport parameters. This method is simple and useful for pulse shape analysis; the result demonstrates promise for the successful application of GAs for the estimation of detector parameters in semiconductor detectors.